Defining Artificial Intelligence - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
The definition of artificial intelligence is prediction [1]. From the dependency of the parameter or variable, the parameter or variable in focus could be predicted as done in [1].  The variable in [1] was predicted from its dependency on a certain variable.